Effect of accessory pigment composition on the absorption characteristics of a dinoflagellate bloom in a coastal embayment - Anil Kumar Vijayan; Srikanth Ayyala Somayajula (Oceanologia, 2014)
The light absorption properties of a dinoflagellate (Noctiluca scintillans Macartney) bloom in Manila Bay were analysed during the onset of a whole-bay-scale bloom in March 2004. The chlorophyll a concentrations varied over a very wide range from 1.4 µg l-1 to extremely high values of 521 µg l-1. The chlorophyll specific absorption coefficients of phytoplankton (a*ph(λ)) varied significantly in shape and magnitude. The spectrally averaged values of a*ph(λ) varied by two orders of magnitude within and outside the bloom patch. The total suspended solid concentration was high in the middle of the bay (≥4 mg l-1). The non-photosynthetic pigment (NPP) index was ~0.6 at most of the stations, mainly due to the presence of photoprotective pigments like zeaxanthin, lutein and neoxanthin, which led to variations in the blue absorption maxima of the chlorophyll-specific absorption coefficients. The absorption properties of the accessory pigments were masked owing to the presence of overlapping pigment absorption bands. The fourth derivative of the absorption spectra was able to resolve these overlapping features and enhance the absorption characteristics of prominent accessory pigments.